RELEVANSI METODE DAN PENDEKATAN PENDIDIKAN ISLAM - Maimunah, Maimunah (Jurnal Ilmiah Peuradeun, 2014)
Seeing the close relationship between the issue of the role of persona thinking educational praxis, especially if the patterns of thought that are innovative and address the needs of the times. Bediuzzaman Said Nursi (Said Nursi) is a man of ideas fundamental and comprehensive, such as educational, political, social, and religious; more so in most of the Risale-i Nur contains many radical ideas and relevant to the current Islamic education. Secondly, there is a kind of line the main idea (philosophical) education as outlined Said Nursi, methods and approaches in an effort to shape the personality and instill the value of education based on the principle teachings of Islam.